Caracterização da atuação de caminhoneiros autônomos no município de Tabuleiro do Norte/CE - Monteiro, Dandara Martins (Universidade Federal Rural do Semi-Árido, 2019)
This research aims to characterize owner-operators from the city of Tabuleiro do Norte / CE, in order to identify their profile by conducting face-to-face interviews. This is justified by the number of existing drivers in the municipality, reaching 78% owner-operators and 22% company drivers. With these results, the research in methodological term was characterized as exploratory-descriptive, with application of a questionnaire to characterize owner-operators, where interviews were conducted with 78 drivers, where 61 are owner-operators and 17 company drivers. The interviewees live in the city of Tabuleiro do Norte / CE, and are associated with ACATAN (Association of Truckers of Tabuleiro do Norte / CE). In order to contribute to the research, as there are not many researches developed in this theme, this paper analyzes the profile of company drivers from the city of Tabuleiro do Norte / CE, which 33% of these professionals are contained in the age group of 31 to 40 years. Regarding the period of professional practice, an interval of 11 to 20 years was estimated, at that is very similar to that obtained by the research conducted by CNT (2019). Truckers travel around the country, but 70% travel the CE / SP route, transporting products such as footwear (26%), food products (24%) and others such as construction material, fabric and less truck load (LTL), and their workday exceeds 10 hours a day, distributed in the morning, afternoon and evening shifts. Finally, it is estimated the value in reais in which it was no longer transported due to the truckers strike, which symbolizes a quantity of approximately 4.537,910 reais/month.
Keywords: Modais de Transporte; Motoristas; Autônomos; Modes of Transport; Drivers; Owner-operators; ENGENHARIAS::ENGENHARIA DE PRODUCAO